Broadening human thermal comfort range based on short-term heat acclimation - Chong, Daokun; Zhu, Neng; Luo, Wei; Zhang, Zhiyu (Energy (Oxford), 2019)
Elevating indoor temperature set-points can reduce cooling energy use. Short-term heat acclimation (HA), the artificially induced adaptation developed in three consecutive days, is an effective method to increase the occupants' acceptance to hot environments. However, the quantitative study on the effects of short-term HA on thermal comfort is lacking. To this end, simulated experiments were conducted in a climate chamber to test the difference of subjects' thermal comfort before and after short-term HA. The subjects were instructed to do intermittent treadmill exercise under hot conditions to reach a HA state. During the trials, core temperature, ratings of perceived exertion (RPE), and ratings of thermal sensation (RTS) were measured. Perceptual strain index (PeSI) was used to assess the effect of short-term HA. The results showed that short-term HA could improve subjects’ adaptability to warmer environments without sacrificing thermal comfort. Furthermore, a HA zone was defined based on the predicted percentage of dissatisfied (PPD) of 10%. The upper limit of the HA zone was 2.1 °C higher than that of the summer thermal comfort zone in ASHRAE Standard 55–2017. This finding suggests that a higher temperature set-point could be considered into the control of air-conditioning systems, contributing to building energy conservation. •Short-term HA can acclimatize occupants to a warmer indoor environment.•Perceptual strain index (PeSI) was used to assess the effect of short-term HA.•The HA zone was defined, which is broader than the summer thermal comfort zone.•The HA zone's boundary is 2.1 °C higher than that of the thermal comfort zone.•It is feasible to appropriately elevate indoor temperature set-points in summer.